2020
DOI: 10.1002/jsfa.10310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tetragenococcus halophilus and Candida versatilis on the production of aroma‐active and umami‐taste compounds during soy sauce fermentation

Abstract: BACKGROUND Soy sauce is a well‐known condiment worldwide. However, the high salt content in soy sauce contributes to the high intake of sodium salt, which usually results in high blood pressure. High salt soy sauce usually has the better quality (aroma and taste) than low salt. Tetragenococcus halophilus and Candida versatilis are important starters for soy sauce fermentation. It is of urgent need to explore what the effect of these two strains on the aroma‐ and taste‐attributes of soy sauce to achieve high qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 50 publications
2
24
1
1
Order By: Relevance
“…PC1 was positively correlated with 2‐furanmethanol, ethyl oleate, 2‐pentylfuran and tridecane, etc., and PC2 was positively correlated with 2‐methylbutanoic acid, 2‐methoxy‐4‐vinylphenol, eugenol and 2‐methyl‐3‐methoxy‐4 h‐pyran‐4‐one, etc. Most of the detected volatiles are characteristic flavors of HLF soy sauce 4,29–31 . A variable importance in projection (VIP) analysis based on the partial least squares discriminant analysis model ( R 2 X = 0.942, R 2 Y = 0.994, Q 2 = 0.981) was implemented to identify the potential variables (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PC1 was positively correlated with 2‐furanmethanol, ethyl oleate, 2‐pentylfuran and tridecane, etc., and PC2 was positively correlated with 2‐methylbutanoic acid, 2‐methoxy‐4‐vinylphenol, eugenol and 2‐methyl‐3‐methoxy‐4 h‐pyran‐4‐one, etc. Most of the detected volatiles are characteristic flavors of HLF soy sauce 4,29–31 . A variable importance in projection (VIP) analysis based on the partial least squares discriminant analysis model ( R 2 X = 0.942, R 2 Y = 0.994, Q 2 = 0.981) was implemented to identify the potential variables (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study that utilized a next-generation high-throughput sequencing-based approach—similar to the approach used in the current study—indicated that the halotolerant and halophilic microbes derived from the sea salt added during fermentation—such as Tetragenococcus, Staphylococcus , and Chromohalobacter spp.—were responsible for Korean soy sauce fermentation [ 15 ]. Tetragenococcus was found in another study to be related to production of aroma-active and umami taste constituents such as aspartic acid, glutamic acid and alanine, indicating its important role in the fermentation of soy sauce [ 31 ]. Consistently, the control soy sauce group in the current study was dominated by halophilic Chromohalobacter and Tetragenococcus spp., whereas the coriander group was dominated by Tetragenococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that host strains might affect the biochemical properties of recombinant enzymes. These changes are crucial for their application as the pH values for most of fermented foods are around 4.5 [54,55].…”
Section: Enzymatic Properties Of Mcob Lsmentioning
confidence: 99%